2012
DOI: 10.1016/j.jalz.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Medical and environmental risk factors associated with frontotemporal dementia: A case‐control study in a veteran population

Abstract: In a clinical sample of veterans, risk of FTD was increased in patients with TBI and marginally decreased in patients with heart disease. Prospective studies are needed to confirm these associations temporally and to identify their underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 40 publications
2
65
1
4
Order By: Relevance
“…FTD is the second most common form of early-onset dementia (Seelaar et al, 2011;Sieben et al, 2012). Several genetic mutations are reported in FTD; however, these findings only explain 20-40% of FTD cases with a positive family history (McKhann et al, 2001;Kalkonde et al, 2012). In the remaining 60-80% of sporadic FTD cases, the true pathophysiological mechanisms remain unclear (McKhann et al, 2001;Seelaar et al, 2011;Kalkonde et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTD is the second most common form of early-onset dementia (Seelaar et al, 2011;Sieben et al, 2012). Several genetic mutations are reported in FTD; however, these findings only explain 20-40% of FTD cases with a positive family history (McKhann et al, 2001;Kalkonde et al, 2012). In the remaining 60-80% of sporadic FTD cases, the true pathophysiological mechanisms remain unclear (McKhann et al, 2001;Seelaar et al, 2011;Kalkonde et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TBI has been implicated as a possible risk factor for several neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease, and amyotrophic lateral sclerosis (ALS) (Maas et al, 2008;Wang et al, 2012a,b). Previous studies suggested an increased risk of frontotemporal dementia (FTD) in patients with TBI (Rosso et al, 2003;Kalkonde et al, 2012); however, because of relatively small sample sizes, they could not exclude recall bias as a factor in the observed association. Therefore, how TBI contributes to FTD remains undetermined.…”
Section: Introductionmentioning
confidence: 93%
“…26 Finally, a study of veterans seen at VA Cognitive Disorders Clinics found that TBIs were more than 4 times more likely to be present in FTD than other forms of dementia such as AD, VaD, and dementia with Lewy bodies. 27 A limitation of prior studies in both veteran and nonveteran populations is that they did not account for the competing risk of death. Our study adds to the existing literature by finding that there is a consistent association between TBI in older veterans and the subsequent risk of developing dementia, even after accounting for mortality as a competing risk.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…28,33 The neuropathology of chronic traumatic encephalopathy, whether seen in athletes with repeated sports injuries or veterans with repeated blast injuries, 34 includes prominent accumulation of tau in the form of neurofibrillary tangles, which are located and distributed differently from the neurofibrillary tangles seen in AD. 28 Furthermore, yet other work has suggested that TBI may predispose individuals to FTD more than other dementias, 27 possibly related to alterations in levels of the protein progranulin that occur after TBI and Table 3 Unadjusted and adjusted risk of dementia from Fine-Gray Cox proportional hazards models Age at dementia diagnosis in veterans with and without TBI, accounting for mortality…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…37,38 While repetitive concussions have been linked to progressive neuropsychiatric symptoms, cognitive deficits, and pathologic tau deposition in the frontal and temporal lobes in chronic traumatic encephalopathy, 39 the relationship of isolated concussion or mild head injury in relation to chronic traumatic encephalopathy and other forms of FTD…”
Section: Environmentalmentioning
confidence: 99%